Charge-transfer states at metal-organic interface limit singlet fission yields: a photonically enhanced pump-probe study - Kolesnichenko, Pavel V.; Hertzog, Manuel; Hainer, Felix; Galindo, Danyellen; Deschler, Felix; Zaumseil, Jana; Buckup, Tiago (The journal of physical chemistry. C, Energy, materials, and catalysis, 2024)
Singlet fission is an exciton-multiplication process that holds promise for next-generation photovoltaic applications. While triplet yields of up to 200% have been reported in thin films of organic fission materials, photovoltaic applications require metal contacts for the generation of photocurrents, which are likely to be impacted not only by triplet fusion and singlet recombination but also by voltage losses at the metal-organic interface and photonic (Purcell) enhancement. Here, we study a series of thin layers of 6,13-bis(triisopropylsilylethynyl)pentacene on silver contacts in open-cavity geometry by using Purcell-enhanced pump-probe spectroscopy. Facilitated by the photonic enhancement, we are able to detect interfacial charge-transfer states and conclude that a significant fraction (40%) of correlated triplet excitons is lost at the metal-organic interface. We further find that although transition rates of singlet fission steps vary with variations of photonic environment, nevertheless, due to the competing nature of channels leading to triplet formation and loss, the resulting singlet fission yields remain unchanged. This is further supported by target analysis of time-resolved spectra and transfer-matrix simulations. These insights on the essential interactions between singlet fission materials in the proximity of metallic contacts are pivotal for the photovoltaic utilization of singlet fission, as efficient extraction of photoexcitations is key to maximizing solar energy harvest.
Gesehen am 13.05.2024